Nadwaga a płaskostopie u dzieci w wieku przedszkolnym – raport z badań = Overweight and flat feet in children of preschool age – research report - Srokowska, Anna; Piernicka, Dorota; Lewandowski, Andrzej; Kowalik, Tomasz; Siedlaczek, Marcin; Srokowski, Grzegorz; Radzimińska, Agnieszka (Journal of Education, Health and Sport, 2015)
Srokowska Anna, Piernicka Dorota, Lewandowski Andrzej, Kowalik Tomasz, Siedlaczek Marcin, Srokowski Grzegorz, Radzimińska Agnieszka. Nadwaga a płaskostopie u dzieci w wieku przedszkolnym – raport z badań = Overweight and flat feet in children of preschool age – research report. Journal of Education, Health and Sport. 2015;5(4):380-404. ISSN 2391-8306. DOI10.5281/zenodo.30565 http://dx.doi.org/10.5281/zenodo.30565 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%284%29%3A380-404 https://pbn.nauka.gov.pl/works/620754 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.03.2015. Revised 05.04.2015. Accepted: 06.04.2015. Nadwaga a płaskostopie u dzieci w wieku przedszkolnym – raport z badań Overweight and flat feet in children of preschool age – research report 1Anna Srokowska, 2Dorota Piernicka, 1Andrzej Lewandowski, 1Tomasz Kowalik, 2Marcin Siedlaczek, 2Grzegorz Srokowski, 2Agnieszka Radzimińska 1Uniwersytet Mikołaja Kopernika w Toruniu Collegium Medicum w Bydgoszczy, Katedra i Zakład Podstaw Kultury Fizycznej, Bydgoszcz, Polska 2Uniwersytet Mikołaja Kopernika w Toruniu Collegium Medicum w Bydgoszczy, Katedra Fizjoterapii, Bydgoszcz, Polska Adres do korespondencji: mgr Anna Srokowska, Katedra i Zakład Podstaw Kultury Fizycznej UMK w Toruniu Collegium Medicum im. L. Rydygiera w Bydgoszczy, ul. Świętojańska 20, 85-077 Bydgoszcz, tel. 600341155, e-mail a.srokowska@cm.umk.pl Słowa kluczowe: nadwaga, płaskostopie, dzieci w wieku przedszkolnym, różnice, zależności. Streszczenie Stopa stanowi bardzo ważny element anatomiczny w ciele człowieka ze względu na swoją funkcję podporowo-nośną. Płaskostopie to wada postawy, która często występuje wśród dzieci, co uwidacznia się podczas badań przesiewowych. Za jedną z przyczyn płaskostopia podaje się obciążenie układu kostno-stawowego nadmierną masą ciała. Celem pracy jest ocena zależności podwyższonego wskaźnika BMI i płaskostopia u dzieci w wieku przedszkolnym. Badaniem objęte zostały dzieci w wieku od 3 do 6 lat z Niepublicznych Przedszkoli „Tęcza” i „Ludzikowo” w Bydgoszczy. Grupa badawcza składała się z 95 dzieci (45 dziewczynek i 50 chłopców). Badania rozpoczęto pomiarami wskaźnika względnej masy ciała BMI. Kolejnym etapem była ocena stanu wysklepienia stóp badanych dzieci, zarówno wysklepienia podłużnego jak i poprzecznego. Pomiary kątów Clarke'a i Wejsfloga umożliwiły odpowiednią klasyfikację. Narzędziem badawczym był tradycyjny podoskop oraz nowoczesne urządzenie RSscan International Footscan. Podwyższone BMI wystąpiło w grupie badawczej jedynie w 6%. Płaskostopie zaś stwierdzono u ponad 1/3 badanych. Uzyskane wyniki badań ze względu na mały odsetek osób z nadwagą i otyłością nie pozwoliły na jednoznaczne powiązanie występowania płaskostopia i zwiększonego wskaźnika BMI. Keywords:, overweight, flat feet, children of preschool age, differences, depending on. Abstract Foot forms the basis of the human anatomy owing to its supporting function. Flat feet is a defect in a posture that is fairly common amongst children and it is shown during health screening. One of the reasons for flat feet is administered load on the bone - joint excess body weight. The main aim of the thesis is to evaluate the relations between elevated BMI and structure of the preschooler's foot. The research spanned children aged between 3 and 6 of non-public nursery ''Tęcza'' and "Ludzikowo" in Bydgoszcz. The experimental group consisted of 95 children (45 girls and 50 boys). The researchers began with measurements of relative body mass index BMI. The next step was to asses the full extent of the children's fallen arches both longitudinal and transverse. The measurement of Clark's and Wejsflog's angles allowed appropriate classification. The research tool included a traditional podoscope and modern device RSscan International Footscan. The percentage of elevated BMI that occurred was six per cent. Flat feet was found in more than one-third of the respondents. Due to the fact that the results concluded small percentage of people with overweight and obesity there is no claim to relate the prevalence of flat feet to an increased BMI.